Marketization, Privatization, and Declining Demographics: Their Impact on Polish Higher Education - Kwiek, Marek (My University, 2013)
The article discusses the increasing marketization and privatization processes in Polish higher education which have been taking place over the last 20 years. This has been spurred on by the dramatic growth of the private sector, the changing relationships between the public and private sectors, and long-term impacts of this relationship on academic norms and codes of behavior. The article considers the Central European private sector institutions as (OECD) ―independent private‖ type of private higher education, generally inexistent in Western Europe. Further, expansion, marketization and privatization are discussed as dominating features of higher education transformation, as well as the future impact of declining demographics on the private sector. Finally, negative consequences of the laissefaire creation of the private sector in the 1990s Poland and its parasitic relationship to public universities are examined.
Keywords: Polish higher education; Poland; marketization; privatization; public-private; private higher education; demographics; declining demographics; public funding; private sector decline; university funding; cost-sharing; Central Europe; higher education policy; public policy; private sector growth; higher education reforms; market reforms